Characterization of symmetric complexes of nerve growth factor and the ectodomain of the pan-neurotrophin receptor, p75NTR. - Aurikko, J; Ruotolo, B; Grossmann, J; Moncrieffe, M; Stephens, E; Leppänen, V; Robinson, C; Saarma, M; Bradshaw, R; Blundell, T (2005)
Nerve growth factor (NGF) is the ligand for two unrelated cellular receptors, TrkA and p75(NTR), and acts as a mediator in the development and maintenance of the mammalian nervous system. Signaling through TrkA kinase domains promotes neuronal survival, whereas activation of the p75(NTR) "death domains" induces apoptosis under correct physiological conditions. However, co-expression of these receptors leads to enhanced neuronal survival upon NGF stimulation, possibly through a ternary p75(NTR) x NGF x TrkA complex. We have expressed human p75(NTR) ligand binding domain as a secreted glycosylated protein in Trichoplusia ni cells. Following assembly and purification of soluble p75(NTR) x NGF complexes, mass spectrometry, analytical ultracentrifugation, and solution x-ray scattering measurements are indicative of 2:2 stoichiometry, which implies a symmetric complex. Molecular models of the 2:2 p75(NTR) x NGF complex based on these data are not consistent with the further assembly of either symmetric (2:2:2) or asymmetric (2:2:1) ternary p75(NTR) x NGF x TrkA complexes.